Induction of protumoral CD11chigh macrophages by glioma cancer stem cells through GM‐CSF. (25th January 2016) - Kokubu, Yasuhiro; Tabu, Kouichi; Muramatsu, Nozomi; Wang, Wenqian; Murota, Yoshitaka; Nobuhisa, Ikuo; Jinushi, Masahisa; Taga, Tetsuya
Abstract : Cancer stem cells (CSCs) are maintained under special microenvironment called niche, and elucidation and targeting of the CSC niche will be a feasible strategy for cancer eradication. Tumor‐associated macrophages (TAMs) are known to be involved in cancer progression and thus can be a component of CSC niche. Although TAMs are known to play multiple roles in tumor progression, involvement of CSCs in TAM development fully remains to be elucidated. Using rat C6 glioma side population (SP) cells as a model of glioma CSCs, we here show that CSCs induce the TAM development by promoting survival and differentiation of bone marrow‐derived monocytes. CSC‐induced macrophages can be separated into two distinct subsets of cells, CD11c low and CD11c high cells. Interestingly, only the CD11c high subset of cells have protumoral activity, as shown by intracranial transplantation into immune‐deficient mice together with CSCs. These CD11c high macrophages were observed in the tumor formed by co‐transplantation with CSCs. Furthermore, CSCs produced GM‐CSF and anti‐GM‐CSF antibody inhibited CSC‐induced TAM development. In conclusion, CSCs have the ability to self‐create their own niche involving TAMs through CSC‐derived GM‐CSF, which can thus be a therapeutic target in view of CSC niche disruption. Abstract : Development of tumor‐associated macrophages (TAMs) is promoted by cancer stem cells (CSCs) via GM‐CSF. CSC‐induced TAMs are separated into two distinct subsets of cells, CD11c low and CD11c high cells. CD11c high TAM but not CD11c low TAM has protumoral activity.